Hygrothermal effect on behaviours on composite materials - Koh, Delia Swee Lin (2019)
The advent use of composites in today’s industry has seen numerous great developments. Composites trump most other materials for their high strength-to-weight ratio. Bismaleimide (BMI) composites have broken the market and are known for its high resistance to hygrothermal degradation. In this study, the hygrothermal effects on woven fibreglass embedded BMI composites are examined. Specimens are hygrothermally aged in three temperature-controlled environments at -5°C, 23°C and 85°C. The sorption curves for each water bath set up were recorded and analysed in comparison with estimates given by two diffusion models – Fickian diffusion model and Langmuir diffusion model. It turned out that all the three set ups exhibited signs of a non-Fickian diffusion process as the Langmuir model’s estimations were more precise. However, both diffusion models in this study failed to account for material breakdown in the case of the 85°C water bath. Additionally, two specimens were removed at four-week intervals and subjected to tensile and flexural tests in order to identify any conclusions regarding hygrothermal ageing and material strength. In conclusion, the flexural and tensile strength of the composite decreased with temperature. The 85°C water bath specimens had the lowest average fracture stresses in both tensile and flexural tests. In relation to the moisture content and the duration of hygrothermal ageing, both tensile and flexural strength of the material improved with increased moisture content. However, this trend is only valid till the point of saturation. Beyond saturation, material mechanical strength decreases as a result of thermal degradation.